Sengketa Ekonomi Syariah: Suatu Kajian Penyelesaian Kasus Sengketa Di Indonesia - Famulia, Ledy; Santina, Rika (Universitas Sang Bumi Ruwa Jurai, 2024)
The settlement of sharia economic disputes through litigation is the authority of the Religious Court. One of the sharia economic decisions is decision Number 1/Pdt.G.S/2024/PA. Lmg. This dispute was filed by PT. Bank Pembangunan Daerah Jawa Timur. Tbk as the plaintiff who sued Anang Fitrianto, S.E as the defendant with a lawsuit for default based on the qard financing extension agreement. This study will analyze the settlement of sharia economic disputes as stated in Decision Number 1/Pdt.G.S/2024/PA. Lmg. The research method used in analyzing the research is a qualitative research method with a normative legal approach and a case approach. This research is descriptive qualitative, the data is analyzed to then draw conclusions using the inductive thinking method. The results of the study concluded that the settlement of sharia economic disputes was in accordance with the formal law and material law of the Religious Courts. This is based on the relative competence and absolute competence of the Religious Courts, the type of contract used, namely the qard contract, and the type of default decision